2015
DOI: 10.1007/s10897-015-9834-8
|View full text |Cite
|
Sign up to set email alerts
|

Uptake of Genetic Counseling, Knowledge of Bleeding risks and Psychosocial Impact in a South African Cohort of Female Relatives of People with Hemophilia

Abstract: In excess of 200 people with hemophilia (PWH) and their families have received genetic counseling (GC) at the Hemophilia Comprehensive Care Centre at Charlotte Maxeke Johannesburg Academic Hospital. However, very few of their at-risk female relatives have attended GC to discuss their reproductive risks and options, or their potential bleeding risks. Limited research has been conducted internationally on factors influencing uptake of GC and testing amongst female relatives of PWH. This prospective study aimed t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
52
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(53 citation statements)
references
References 23 publications
1
52
0
Order By: Relevance
“…Recent findings suggest that women who are heterozygous for factor VIII mutations, commonly known as haemophilia carriers, may also have significant bleeding symptoms and lower health-related quality of life (HR-QoL) 11 12. In fact, 30% of haemophilia carriers have low coagulation factor levels and may experience excessive bleeding 1 3.…”
Section: Introductionmentioning
confidence: 99%
“…Recent findings suggest that women who are heterozygous for factor VIII mutations, commonly known as haemophilia carriers, may also have significant bleeding symptoms and lower health-related quality of life (HR-QoL) 11 12. In fact, 30% of haemophilia carriers have low coagulation factor levels and may experience excessive bleeding 1 3.…”
Section: Introductionmentioning
confidence: 99%
“…Fewer studies have specifically evaluated the prevalence of screening and identified the reasons why screening or counselling was lacking. These studies reported that the prevalence of screening ranged from 41% to 49% with the exception of a single study reporting 69% of screening, meaning that only a limited fraction of potential carriers received information from a haemophilia specialist about their status and underwent coagulation factor analysis. However, these statistics must be considered with care, as the inclusion criteria and objectives all differed among these studies.…”
Section: Promotion Of Carriers Screeningmentioning
confidence: 99%
“…It has been estimated that for each male with hemophilia, there are five potential female carriers [3]. Carriers are at risk of having sons with hemophilia but may also carry a bleeding risk [4].…”
Section: Introductionmentioning
confidence: 99%
“…As circumcision generally represents the first surgical intervention in African boys with hemophilia, it is a major cause of bleeding and death [16]. Unawareness of carrier condition and bleeding risk, as well as healthcare givers’ ignorance concerning appropriate management modalities, are also major issues of concern in these countries [4, 17]. In Sub-Saharan Africa, little is known about hemophilia carriers [3, 4, 18, 19], with only very limited access to molecular testing [18, 20], and pedigree and clotting FVIII and IX analyses being often the principal screening and assessment tools.…”
Section: Introductionmentioning
confidence: 99%